New alternative ingredients and genetic selection are the next game changers in rainbow trout nutrition: a metabolomics appraisal - Simon Roques; Catherine Deborde; Sandrine Skiba-Cassy; Françoise Médale; Mathilde Dupont-Nivet; Florence Lefevre; Jérome Bugeon; Laurent Labbé; Yann Marchand; Annick Moing; Benoit Fauconneau (Scientific Reports, 2023)
Abstract The formulation of sustainable fish feeds based on plant ingredients supplemented by alternative ingredients to plant (insect, micro-algae, yeast) and genetic selection of fish for plant-based diets were tested on rainbow trout in two separate experiments. Plant-based diets and corresponding diets supplemented with an ingredient mix: insect, micro-algae and yeast in Experiment A, and insect and yeast in Experiment B were compared to commercial-like diets. In experiment A, the mix-supplemented diet was successful in compensating the altered growth performance of fish fed their respective plant-based diet compared to those fed the commercial diet, by restoring feed conversion. In experiment B, the selected line demonstrated improved growth performances of fish fed mix-supplemented and plant-based diets compared to the non-selected line. Metabolomics demonstrated a plasma compositional stability in fish fed mix-supplemented and basal plant-based diets comprising an amino acid accumulation and a glucose depletion, compared to those fed commercial diets. The selected line fed mix-supplemented and commercial diets showed changes in inositol, ethanol and methanol compared to the non-selected line, suggesting an involvement of microbiota. Changes in plasma glycine-betaine content in fish fed the mix-supplemented diet suggest the ability of the selected line to adapt to alternative ingredients.